Supporting Those Who Provide Support: What Do University Student-Facing Staff Say About Training for Working with Diverse Cohorts? - Samantha Kilmartin; Tessa McCredie; Sally Baker; Farhana Laffernis; Clemence Due (Student Success, 2024)
Increasing access for underrepresented cohorts to higher education has long been a priority internationally, and Australia is no exception. While universities offer a range of services in the areas of Equity, Career Development and Academic Advising (ECDAA) to support student success, there is little understanding of how these student-facing support staff are supported to work with diverse student cohorts. This is particularly the case when working with cultural and linguistic marginalised (CALM) students such as international students, refugees or migrants. This article examines the differing levels of knowledge and experience ECDAA practitioners’ have in working with culturally and linguistically diverse students in Australian universities, and the challenges practitioners face in accessing professional development to support them in their roles. While the importance of tailoring support services to meet the needs of diverse student cohorts is recognised, our findings highlight the need to provide ongoing professional development to support practitioners in the delivery of nuanced support services to CALM students.